Endoplasmic Reticulum Stress and the Unfolded Protein Response in Cerebral Ischemia/Reperfusion Injury - Wang, Lei; Liu, Yan; Zhang, Xu; Ye, Yingze; Xiong, Xiaoxing; Zhang, Shudi; Gu, Lijuan; Jian, Zhihong; Wang, Hongfa (Frontiers in Cellular Neuroscience, 2022)
Ischemic stroke is an acute cerebrovascular disease characterized by sudden interruption of blood flow in a certain part of the brain, leading to serious disability and death. At present, treatment methods for ischemic stroke are limited to thrombolysis or thrombus removal, but the treatment window is very narrow. However, recovery of cerebral blood circulation further causes cerebral ischemia/reperfusion injury (CIRI). The endoplasmic reticulum (ER) plays an important role in protein secretion, membrane protein folding, transportation and maintenance of intracellular calcium homeostasis. Endoplasmic reticulum stress (ERS) plays a crucial role in cerebral ischemia pathophysiology. Mild ERS helps improve cell tolerance and restore cell homeostasis; however, excessive or long-term ERS causes apoptotic pathway activation. Specifically, the protein kinase R-like endoplasmic reticulum kinase (PERK), activating transcription factor 6 (ATF6), and inositol-requiring enzyme 1 (IRE1) pathways are significantly activated following initiation of the unfolded protein response (UPR). CIRI-induced apoptosis leads to nerve cell death, which ultimately aggravates neurological deficits in patients. Therefore, it is necessary and important to comprehensively explore the mechanism of ERS in CIRI to identify methods for preserving brain cells and neuronal function after ischemia.